Indicators of motor activity and physical fitness of university teachers - Tretyakov, A.A.; Akulova, L.N.; Nikulina, T.V.; Klimova, V.K. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the level of physical fitness of university teachers based on the analysis of their physical activity. Methods and structure of the study. The pedagogical experiment was carried out on the basis of the Belgorod State National Research University, which was attended by teachers of the humanities (general profile) and physical education. The sample consisted of participants aged 30 to 35 years. To assess motor activity, OMRON pedometers were used. To assess physical fitness, control exercises for men and women were proposed. Results and conclusions. It has been established that teachers of humanitarian disciplines are characterized by low motor activity, which is associated with the peculiarities of their professional activities. This indicates a weak functional activity of the body systems and a violation in the activity of regulatory mechanisms. The authors proposed ways to increase motor activity and increase efficiency.